Dietary Antioxidant Indices in Relation to All-Cause and Cause-Specific Mortality Among Adults With Diabetes: A Prospective Cohort Study - Wang, Wenjie; Wang, Xiaoyan; Cao, Shiling; Duan, Yiting; Xu, Chengquan; Gan, Da; He, Wei (Frontiers in Nutrition, 2022)
Background The potential beneficial effect of individual antioxidants on mortality has been reported. However, the association of overall intakes of dietary antioxidants with all-cause and cause-specific mortality among adults with diabetes remained unclear. Methods A total of 4,699 US adults with diabetes were enrolled in 2003–2014 in the National Health and Nutrition Examination Survey (NHANES) and followed for mortality until 31 December 2015. The Dietary Antioxidant Quality Score (DAQS) and the Dietary Antioxidant Index (DAI), which indicate the total antioxidant properties, were calculated based on the intakes of vitamins A, C, E, zinc, selenium, and magnesium. The Cox proportional hazards regression models were used to investigate the associations of the DAQS or the DAI with all-cause and cause-specific mortality. Results A total of 913 deaths occurred during 27,735 person-years of follow-up, including 215 deaths due to cardiovascular disease (CVD) and 173 deaths due to cancer. The higher intakes of antioxidant vitamins A, E, magnesium, and selenium were associated with lower all-cause mortality. The adjusted hazard ratios (HRs) (95% CIs) comparing the highest DAQS (5–6) to the lowest DAQS (0–2) were 0.70 (0.53–0.92) for all-cause mortality, 0.56 (0.35–0.90) for CVD mortality, and 0.59 (0.33–1.04) for cancer mortality. Consistent inverse associations were found between the DAI and mortality. Conclusion Higher intake of overall dietary antioxidants was associated with lower risk of death from all-cause and CVD in adults with diabetes. Future dietary intervention studies are needed to determine whether increasing overall antioxidant micronutrients intake could prevent premature death among adults with diabetes.